Faktor-faktor yang Mempengaruhi Kemauan untuk Membayar Pajak dengan Kesadaran Membayar Pajak sebagai Variabel Intervening - Haedar Haedar; Rismawati Rismawati (Equilibrium : Jurnal Ilmiah Ekonomi, Manajemen dan Akuntansi, 2014)
This research aimed to find factor that affect willingness to pay taxes, case study on individual taxpayers who perform as a freelancer that registered at KPP Pratama Palopo. As these factors are the realization of tax paying knowledge and understanding of taxation laws, and a good perception of the effectiveness of the tax system. This research uses quantitative research methods, where the data obtained from questionnaires. After the data collected by using random sampling , the data was analyzed. Test statistic used is multiple linier regression test, and data obtained were processed using SPSS statistical software.